Appendix to Assessing the Value of Branches with What-if Analysis - Bird, Christian; Zimmermann, Thomas; Zimmermann, Tom (2012)
Our research paper, “Assessing the Value of Branches with What-If Analysis” contained an intuitive description of our method of creating alternative histories with branches removed and using these alternative histories along with the original history to calculate delay and provided isolation. This appendix contains a more precise formal description of our technique and metrics for the interested reader.